2019
DOI: 10.5897/ijps2019.4794
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sedimentary thickness using spectral analysis of aeromagnetic data over Otukpo and Ejekwe areas of the lower Benue Trough, Nigeria

Abstract: The aeromagnetic data of Otukpo (sheet 270) and Ejekwe (sheet 289) areas of the lower Benue Trough of Nigeria were interpreted quantitatively. The quantitative interpretation employed spectral analysis technique with the aim of locating specific basement depths to buried magnetic source rocks in the study area. First order polynomial fitting was adopted for regional-residual separation of the total magnetic intensity (TMI) map. The result of the spectral analysis indicates two depth source models; with depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The map shows preferential enrichment of Uranium to Thorium dominantly at the western part of Otukpo and at the eastern part of Ankpa. The rocks in the Otukpo area were identified as sandstones and shale, which agrees with the geology of the Lower Benue Trough (Reyment, 1965;Ofoegbu, 1985;Obaje, 2009;Asielue et al, 2019). Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The map shows preferential enrichment of Uranium to Thorium dominantly at the western part of Otukpo and at the eastern part of Ankpa. The rocks in the Otukpo area were identified as sandstones and shale, which agrees with the geology of the Lower Benue Trough (Reyment, 1965;Ofoegbu, 1985;Obaje, 2009;Asielue et al, 2019). Fig.…”
Section: Resultssupporting
confidence: 77%
“…Most of the geophysical works carried out in the basin employed airborne magnetic investigations for spectral depth or sedimentary thickness determinations (Igwesi & Umego, 2013;Ike et al, 2017;Alasi et al, 2017;Ugwu et al, 2018;Asielue et al, 2019;Okoro et al, 2021). Hence, an aeroradiometric investigation of the area is important in order to evaluate the mineralization in the area from the relative abundance of these three radionuclides of Uranium, Thorium and Potassium.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that this part of the Lower Benue Trough may not hold promise in terms of hydrocarbon accumulation. Other investigations in the study area includes; geological investigation for minerals deposit (Asielue et al, 2019;Uzuakpunwa, 1774;Olade, 1975;Hoque, 1984,). Structural features which control the anomalous mineralization have also been delineated by many researchers (Olade, 1976;Ofoegbu, 1984).…”
Section: Introductionmentioning
confidence: 96%